76.3k views
0 votes
3.) rewrite r(x) in expanded form

3.) rewrite r(x) in expanded form-example-1
User Tomjen
by
5.3k points

2 Answers

1 vote

Answer:


{\huge{\pink{\underline{\underline{QuEsTiOn}}}}}

rewrite r(x) in expanded form


{\huge{\pink{\underline{\underline{SoLuTiOn}}}}}


(x-3)(x+5)\\</p><p>=>x(x + 5) - 3(x + 5) \\</p><p>= > {x}^(2) + 5x - 3x + 15\\</p><p> => {x}^(2) + 2x + 15

User Argoth
by
4.1k points
5 votes

Answer:

Explanation:

r(x)= (x-3)(x+5)

= x²+5x-3x-15

=x²+2x-15

User GRESPL Nagpur
by
5.3k points